Human uterus myoma and gene expression profiling: A novel in vitro model for studying secretory leukocyte protease inhibitor-mediated tumor invasion. Issue 1 (28th August 2016) - Mikami, Yoshikazu; Fukushima, Atsushi; Komiyama, Yusuke; Iwase, Takashi; Tsuda, Hiromasa; Higuchi, Yasuhiko; Hayakawa, Satoshi; Kuyama, Kayo; Komiyama, Kazuo
Highlights: The myoma model provides a biologically relevant matrix for tumor invasion studies. Ca9-22 but not SLPI-deficient Ca9-22 cells invade into myoma tissue. SLPI plays an important role in Ca9-22 cell invasion in conjunction with MMPs. Gene expression profiling shows candidates playing in SLPI-mediated tumor invasion. Abstract: Secretory leukocyte protease inhibitor (SLPI) is a serine protease inhibitor that diminishes tissue destruction during inflammation. A recent report revealed high levels of SLPI expression in the oral carcinoma cell. In addition, overexpression of SLPI up-regulates metastasis in lung carcinoma cells. On the other hand, matrix metalloproteinases (MMPs) are proteinases that participate in extracellular matrix degradation. SLPI and MMPs are involved as accelerators of the tumor invasion process; however, their exact roles are not fully understood. Understanding the mechanism of tumor invasion requires models that take the effect of microenvironmental factors into account. In one such in vitro model, different carcinoma cells have been shown to invade myoma tissue in highly distinct patterns. We have used this myoma model, as it provides a more natural stroma-like environment, to investigate the role of SLPI in tumor invasion. Our results indicate that the model provides a relevant matrix for tumor invasion studies, and that SLPI is important for the invasion of oral carcinoma Ca9-22 cells in conjunction with MMPs. Furthermore, using bioinformatics analysis, we have identified candidates as key molecules involved in SLPI-mediated tumor invasion.